PENGETAHUAN IBU HAMIL TENTANG PENANGANAN KEDARURATAN EKLAMPSIA PADA IBU HAMIL DI RUMAH SAKIT UMUM DAERAH SIDIKALANG - Jojor Silaban; Risdiana Melinda Naibaho; Verawaty Fitrinelda Silaban (Universitas Prima Indonesia, 2023)
Abstract In Indonesia, severe pre-eclampsia and eclampsia contribute to maternal mortality ranging from 1.5% to 25%, while infant mortality is between 45% to 50%. Eclampsia is an acute disorder in pregnant women, at 20 weeks gestation or more or during the puerperium which is characterized by seizures or coma, previously preceded by signs of pre-eclampsia. The incidence of pre-eclampsia and eclampsia in North Sumatra according to Riskesdas 2018 is 0.2% or the same as the national prevalence. Accuracy in making decisions in seeking antenatal health services greatly determines the prognosis or success in preventing maternal deaths due to pre-eclampsia and eclampsia. The purpose of this study was to determine the knowledge of pregnant women about emergency management of eclampsia in pregnant women at the Sidikalang Regional General Hospital, Dairi Regency 2021. This research is a descriptive observational survey study, conducted at the Sidikalang Regional General Hospital in May and ends in December 2021. The population in this study were pregnant women from May to November 2021 who came to check their pregnancy at the Obgyn Polyclinic of the Regional General Hospital. Sidikalang as many as 1106 people. In this study, the number of samples was 10% of the total population, namely 111 people. The results showed that the knowledge of pregnant women about emergency management of eclampsia in pregnant women was less than 64 people (57.66%) and sufficient knowledge was 35 people (31.53%) and good knowledge was only 12 people (10.81%). ). The conclusion that the knowledge of pregnant women about the emergency management of eclampsia at the Sidikalang Regional General Hospital in 2021 is less by 57.66%.